(3x+2)(4x-3)=10x(x+1)

Simple and best practice solution for (3x+2)(4x-3)=10x(x+1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (3x+2)(4x-3)=10x(x+1) equation:


Simplifying
(3x + 2)(4x + -3) = 10x(x + 1)

Reorder the terms:
(2 + 3x)(4x + -3) = 10x(x + 1)

Reorder the terms:
(2 + 3x)(-3 + 4x) = 10x(x + 1)

Multiply (2 + 3x) * (-3 + 4x)
(2(-3 + 4x) + 3x * (-3 + 4x)) = 10x(x + 1)
((-3 * 2 + 4x * 2) + 3x * (-3 + 4x)) = 10x(x + 1)
((-6 + 8x) + 3x * (-3 + 4x)) = 10x(x + 1)
(-6 + 8x + (-3 * 3x + 4x * 3x)) = 10x(x + 1)
(-6 + 8x + (-9x + 12x2)) = 10x(x + 1)

Combine like terms: 8x + -9x = -1x
(-6 + -1x + 12x2) = 10x(x + 1)

Reorder the terms:
-6 + -1x + 12x2 = 10x(1 + x)
-6 + -1x + 12x2 = (1 * 10x + x * 10x)
-6 + -1x + 12x2 = (10x + 10x2)

Solving
-6 + -1x + 12x2 = 10x + 10x2

Solving for variable 'x'.

Reorder the terms:
-6 + -1x + -10x + 12x2 + -10x2 = 10x + 10x2 + -10x + -10x2

Combine like terms: -1x + -10x = -11x
-6 + -11x + 12x2 + -10x2 = 10x + 10x2 + -10x + -10x2

Combine like terms: 12x2 + -10x2 = 2x2
-6 + -11x + 2x2 = 10x + 10x2 + -10x + -10x2

Reorder the terms:
-6 + -11x + 2x2 = 10x + -10x + 10x2 + -10x2

Combine like terms: 10x + -10x = 0
-6 + -11x + 2x2 = 0 + 10x2 + -10x2
-6 + -11x + 2x2 = 10x2 + -10x2

Combine like terms: 10x2 + -10x2 = 0
-6 + -11x + 2x2 = 0

Factor a trinomial.
(-1 + -2x)(6 + -1x) = 0

Subproblem 1

Set the factor '(-1 + -2x)' equal to zero and attempt to solve: Simplifying -1 + -2x = 0 Solving -1 + -2x = 0 Move all terms containing x to the left, all other terms to the right. Add '1' to each side of the equation. -1 + 1 + -2x = 0 + 1 Combine like terms: -1 + 1 = 0 0 + -2x = 0 + 1 -2x = 0 + 1 Combine like terms: 0 + 1 = 1 -2x = 1 Divide each side by '-2'. x = -0.5 Simplifying x = -0.5

Subproblem 2

Set the factor '(6 + -1x)' equal to zero and attempt to solve: Simplifying 6 + -1x = 0 Solving 6 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + -1x = 0 + -6 Combine like terms: 6 + -6 = 0 0 + -1x = 0 + -6 -1x = 0 + -6 Combine like terms: 0 + -6 = -6 -1x = -6 Divide each side by '-1'. x = 6 Simplifying x = 6

Solution

x = {-0.5, 6}

See similar equations:

| 0=3x^2-6+11x+14x^2-3x | | x^3=30x | | (10+x)*2=x-4 | | (X+10).2=x-4 | | 4a^2b+2ab=0 | | 4x^2-3600=0 | | 2a+8.9=5.4a-15.24 | | 9x+12y=225 | | 8a^2+6a=15 | | 0=3x^2+2x-9-11x^2 | | 11-2x-7-4x=6 | | 3x-4x=-12 | | (5a-7)=(6a+5) | | 19540-23150= | | Y-5=23 | | -9+x/4=-7 | | 5k=12+2k | | 170*11= | | x/10+4=5 | | -7+4x=-15 | | 7X-(3X+5)=2X-39 | | -12x+4=100 | | 1.2x-0.5=20 | | 6n+24=4n | | -12+4=100 | | (z^2+5z+8)(z^2+2z+6)=50000000000000000000000 | | 4(1/2)-9=-9 | | 4+4N=2N+6 | | 11p=54+5p | | 4x^2-33x+31=-8x+6 | | X+5=-x-13 | | 4+N=2N+6 |

Equations solver categories